Risk‐taking in vaccination, surgery, and gambling environments: Evidence from a framed laboratory experiment. (29th December 2017) - Binder, Simon; Nuscheler, Robert
Abstract: Vaccination involves a tradeoff between two risky alternatives, namely, susceptibility and immunization. By designing a controlled laboratory experiment, we investigate the association between risk preferences and immunization decisions. To contrast the role of risk preferences in vaccination decisions with other domains, we implemented four frames: vaccination, surgery, complex neutral, and simple neutral. We found direct framing effects for females but not for males. For the former, the demand for the safer alternative is significantly larger in the surgery frame than in all other frames. For male subjects, we found a significant association between stated risk preferences and choice behavior in the simple neutral frame but not in the other three frames. For female subjects, we observed the exact opposite. Although the complexity of the decision problem matters, there is no indication of differential roles of risk preferences for a given complexity. We found that the share of consistent choices is significantly larger in the surgery frame as compared to the two neutral frames, that is, context improves decision making. This does not apply to the vaccination frame, so there is something about vaccinations that prevents individuals from better understanding the decision problem at hand.